UNDERWATER ARCHEOLOGY IN AZERBAIJAN: CURRENT STATE AND PROSPECTS - Rustamova, Lejla Mamed gyzy; Seidov, Abbas Gadir oglu; Mamedova, Ajgun Musa gyzy (History, Archeology and Ethnography of the Caucasus, 2025)
The article discusses archaeological research conducted within the Azerbaijani sector of the Caspian Sea over a period spanning nearly nine decades. Underwater archaeological investigations in the territory of Azerbaijan can be categorized into four chronological phases: 1) 1938-1940, 1946, and 1962; 2) 1968-1987; 3) 2008; and 4) 2022-2024. The primary archaeological investigations of the initial phase were undertaken in 1939 under the direction of Professor E.  Pakhomov, in collaboration with archaeologists I. Jafarzade and O. Ismizade. This research focused on the island of Bayil Qasri, also known as Sabail City, situated approximately 300-350 meters southwest of the Baku coastline, as well as on the adjacent seabed. During the second phase (1968-1987), Z. Yampolsky served as a consultant, and diving operations were executed by V. Kvachidze. These efforts led to the identification of over 4,000 material and cultural artifacts, along with the potential localization of submerged settlements. The third phase, conducted by archaeologist I. Aliyev in 2008 on the Absheron Peninsula, approximately 500 meters from a site known as Shahri-Gurgan, documented the underwater remains of a medieval settlement and its associated cemetery. The fourth phase commenced in 2022. Consequent to the decline in the water level of the Kura River during 2022-2023, archaeologist M. Mustafayev undertook the investigation of pitcher burials and domestic artifacts in the villages of Pirabba and Shorkand within the Neftchala region. Subsequently, in August-September 2024, an expedition under the leadership of Professor A. Seyidov conducted archaeological reconnaissance in the deeper areas of the Caspian Sea, off the coast of Zira and Pirallahi on the Absheron Peninsula. This expedition resulted in the discovery of pottery dating from the 12th to the 14th centuries and the remnants of two shipwrecks from the 19th century. Photographs of Gashtasbi and Mahmudabad silver dirhams, housed within the Numismatics Fund of the National Museum of History of Azerbaijan, have been included in this article. The analysis of these discoveries facilitates the determination of coin denominations prevalent in Azerbaijan during the 14th and 15th centuries and aids in tracing the political and economic history of the period.
Keywords: underwater archeology; Caspian Sea; Gashtasbi; Mahmudabad; Kura; silver dirham